Knowledge, Attitude and Health Behavior of Dental Students towards HIV Patients - Rayia J Al-Naimi; Ghada D Al-Saygh (University of Mosul, College of Dentistry, 2009)
Aim: To investigate a group of Iraqi dental students knowledge about HIV infection, attitudes towardstreating HIV/AIDS patients and behavior practices. Materials and Methods: The study populationconsisted of 220 dental students from University of Mosul, College of Dentistry who were treatingpatients in the clinics of the College. The survey instrument was a self-administered questionnaire.Results General and knowledge of the oral and other conditions related to AIDS patient was low, studentsattitude towards treating HIV patient was low (167) refused to treat such patient with a highlysignificant difference, most of the students (160) were willing to treat HBV (hepatitis B patient ) comparedto only 60 that agreed to treat HIV patient , (32.7%), of the student had experienced a needlestick injury, (65.9%) of the students stated that an AIDS patient should be referred to a supportinggroup to provide him with dental treatment. A significant difference in the number and percentage ofstudents that knew they needed to undertake precautionary measures in treating patients which was 213compared to 7 students only. The three types of barrier technique during routine work was not undertakenby any of the students, 213 students i.e. (96.4%) required more knowledge concerning infectioncontrol, cross infection, modes of transmission of the disease. Conclusions: These findings clearlyhighlights the importance of the teaching emphasis of dental educators on the disease, it is vital thatuniversal precautions also should be adopted through faculty policy and reinforced at an early level ofstudy, so that the barrier techniques become a protocol and a norm in their daily practices as clinicians.Because of certain inadequacies in knowledge and infection control practices among respondents, acurriculum focusing on the management of HIV/AIDS, including infection for all blood borne diseasesis recommended.